PRODUKSI DAN KARAKTERISASI SILIKA SEBAGAI MATERIAL MULTIFUNGSI DARI LIMBAH JAGUNG - Ayu Dahliyanti; Ika Dyah Widharyanti; Catia Angli Curie (JURNAL TEKNOLOGIA, 2019)
In order to prevent negative environmental impact, high volume of waste generated from corn processing needs to be transformed into a more valuable product. Based on the mineral composition of corn plant, this waste could become a potential source of silica, a multifunctional material with applications in various fields, such as semiconductor, adsorbent technology, catalysis, and lithium ion battery. In this work, corn husks, cobs, and stalks is processed through leaching at various HCl concentration, followed by atmospheric decomposition at moderate temperature to obtain silica for further suitable application. Morphological characteristic is analyzed by SEM images, crystallinity of silica is determined by XRD, while purity and possible organic contaminants are investigated by FTIR. The result shows that corn husks provide the highest silicon dioxide yield at 2.543 wt.%. Powders obtained from corn husks also indicate a higher purity with insignificant metallic or organometallic contaminants, showing closest crystal structure to the mixture of quartz and amorphous phase.